2013
DOI: 10.1002/lary.24508
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in head and neck cancer patients: Impact of HPV and primary treatment modality

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 23 publications
6
48
0
Order By: Relevance
“…Additionally, our study confirms the previous findings that p16 positive cases have better quality of life over their counterparts [21], often attributed to improved survival, younger age and lack of smoking, although other studies have found no difference [22].…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 91%
“…Additionally, our study confirms the previous findings that p16 positive cases have better quality of life over their counterparts [21], often attributed to improved survival, younger age and lack of smoking, although other studies have found no difference [22].…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 91%
“…Maxwell et al [33] showed that p16-positive head and neck squamous cell carcinoma patients have better QoL scores at baseline irrespective of the treatment modality compared with the p16-negative counterparts. The HPV-positive patients had worse salivary function in the early stage of recovery than HPV-negative counterparts.…”
Section: Discussionmentioning
confidence: 98%
“…On multivariate analysis controlling for tumor site, this association did not remain significant. Lately, Maxwell et al [70] determined the posttreatment QOL (using same questionnaire as our study) in the head and neck cancer (including OCSCC and OPC) patients, classifying by HPV status and primary treatment modality (surgical vs nonsurgical) and showed that HPV patients had better QOL scores in speech (P = 0.0009), chewing (P = 0.0004), and swallowing (P = 0.021) after 1 year posttreatment compared to HPV-negative patients. Primary treatment modality did not affect overall QOL or any of the QOL categories in HPV-positive patients.…”
Section: Discussionmentioning
confidence: 99%